FAKTOR PENGGUNAAN ALAT KONTRASEPSI PADA PASANGAN USIA SUBUR DI PROVINSI DKI JAKARTA TAHUN 2022 (DATA SEKUNDER SUSENAS 2022) - Muhammad Sulthan Fadhil (2024)
Contraceptive use among childbearing age couples (PUS) in Indonesia tends to stagnate, ranging between 55%-56% over the last three years. This achievement is still far from the target of 62.92% of couples using contraception by 2023. The aim of this study was to analyze the factors that influence the use of contraceptives in PUS in DKI Jakarta in 2022. This study used a cross-sectional study design with secondary data from Susenas 2022. The population in this study was PUS (15-49 years), while the sample was PUS residing in DKI Jakarta with complete data, totaling 1.824.194 respondents after weighting. Data analysis was performed using chi-square and multiple logistic regression test. The results showed that there were three variables that were closely related as factors in the use of contraceptives: age (p=0,000), occupation (p=0,000), and education (p=0,000). Furthermore, it showed that higher education was the most influential factor on the use of contraceptives among PUS in DKI Jakarta in 2022 (p=0,000; POR=1,9; 95% CI 1,893-1,934). The government is expected to collaborate with companies to provide more education and contraceptive services to working PUS, including through health/family planning (KB) clinics in companies.